Seasonal and annual variation in the diving behaviour of Hutton's shearwater (Puffinus huttoni). Issue 4 (1st October 2020) - Bennet, Della G.; Horton, Travis W.; Goldstien, Sharyn J.; Rowe, Lindsay; Briskie, James V.
ABSTRACT: With the development and implementation of tracking technology, we are now able to monitor the foraging behaviour of seabirds while at sea. Time-Depth Recorders (TDRs) were fitted to Hutton's shearwaters ( Puffinus huttoni ), an endangered endemic New Zealand species, to measure how diving behaviour varies over the breeding cycle. Hutton's shearwaters (∼350 g) dive up to 339 times per day (average 68.8) at depths to 35 m (average 5.6 m), and for periods up to 60 s (average 19.2 s). Incubating birds dived deeper than birds feeding chicks, and a significant difference in diving depth and dive duration were detected at different times of the day. Neither dive frequency nor dive duration differed significantly between years, but there was some annual variation in dive depths. The temporal variation we observed in the diving behaviour of Hutton's shearwaters suggests they are likely to exploit different types of pelagic prey at different stages in their breeding cycle. With on-going changes in the marine environment, monitoring changes in feeding behaviour using TDRs may provide a way to assess environmental change and improve the conservation of this species.